The impact of income redistribution on the composition of output demand - Lim, Joseph Y.; Bautista, Carlos (1986)
This study employed the 1979 Input-Output table, the 1975 Family Income and Expenditures Survey, and the National Income Accounts of 1979 to study the effect of income redistribution on the composition of output demand. It was hoped that a significant amount of redistribution from the rich to the poor could make the whole economy less import-dependent and more labor-intensive. The results, however, did not come up to expectations. The positive effects on exports, labor-intensiveness and balance of trade were miniscule, if any. To explain the study's results the authors have put forward the following reasons, namely: 1) the static nature of the input-output framework that precludes dynamic and structural changes om the backward and forward linkages in the economy; 2) the offsetting effects of a rise up in stature; and 3) the assumption that investment demands are not affected by income redistribution and changes in output demand.
Keywords: Income distribution